Impact of Demonetization on the Various Sectors of Indian Economy - Dr. Vinay Chandra; Surabhi Srivastava; Mayank Jindal (International Journal of Engineering and Management Research, 2020)
Demonetisation is an act of cancelling the legal tender status of a currency unit. It is a process when the government pulled out a unit of currency from the total circulation of the economy. The concept of demonetisation is not new, at first French used demonetisation then after most of the countries has adopted demonetisation to clean up the economy from corruption and inflation. India has adopted demonetisation three times: At first in January 1946 when RBI demonetised Rs. 1000 and Rs. 10000 currency notes. and again in 1978 by Moraji Desai of Rs. 1000, 5000, 10000 banknotes were demonetised and both demonetisation were held to eradicate black money. But the term Demonetisation became familiar on 8 November 2016 when P.M. Mr Narendra Damodar Das Modi announced Rs.500 and Rs.1000 currency notes will be no longer as legal tender status from the past midnight to unearth the corruption, black money and terror funding. Therefore this research paper is an attempt to throw the light on effect of demonetisation launched by NDA Government.